Utilizing and evaluating of virtual tours in art exhibition amidst global pandemic / Nur Muhammad Amin Hashim Amir - Hashim Amir, Nur Muhammad Amin (Faculty of Art and Design, 2021)
Covid-19 has sojourned the world as we know then into a cessation. It affects various disciplinary fields to a standstill which includes art and tourism. In Malaysia, to adapt to the global pandemic; new opportunities have emerged and dealt with it no longer becomes optional but rather a solution. Therefore, this research is mainly focused on implementing virtual tours to cope with the new norms; and evaluates its implication specifically in showcasing art exhibitions. The researcher uses the concept of Google Street View to capture virtual spaces; combining with Pano2Vr software as constructing tools; for audiences to interact and discusses its usefulness based on their ease of accessibility. Through the usage of this software, the researcher was able to reconstruct the actual gallery into series of interconnected images that trajectories within a web hosting server which are accessible over various platforms. The researcher purposely uses 360 panoramic images to maintain the ingenuity and actuality of the exhibition surroundings; due to most audiences are more complacent to the practicality compared to 3D digital replication. The advantages and disadvantages of this particular application of Virtual Tours (VTs) are then assessed through data collected based on the accessed devices, accessed locations, and total participation to see whether this concept can be used as a new alternative tool in showcasing art exhibitions in the effort of avoiding the pandemic widespread while still keeping the art activity at a sensible pace.